2021
DOI: 10.1111/infa.12416
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal transactional relations among young children’s defiance and committed compliance and maternal assertive control

Abstract: The main goal of this study was to more closely understand the direction of relations between maternal behavior and young children's defiance and committed compliance. We examined 256 mother–child dyads to explore developmental transactional relations between maternal assertive control, children's committed compliance, and children's defiance at 18 (T1), 30 (T2), and 42 (T3) months of age. After controlling for maternal gentle control, SES, and child sex, results showed parent effects for children's committed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Additionally, expressions of warmth were negatively related to toddlers' emotional reactivity and noncompliance. Thus, our findings are in parallel with previous research in different cultures showing that providing warmth and support during disciplinary interactions promotes children's compliance with parental rules (Chen et al, 2003); additionally, a lack of warmth and support may dysregulate children and result in defiant responses to requests (Xu et al, 2021). We also found that higher maternal warmth was a moderator, weakening the positive relation between power assertive discipline and children's emotional reactivity, which aligns with previous research on the role of warmth as a support or buffer in disciplinary interactions (Deater‐Deckard et al, 2006; McKee et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, expressions of warmth were negatively related to toddlers' emotional reactivity and noncompliance. Thus, our findings are in parallel with previous research in different cultures showing that providing warmth and support during disciplinary interactions promotes children's compliance with parental rules (Chen et al, 2003); additionally, a lack of warmth and support may dysregulate children and result in defiant responses to requests (Xu et al, 2021). We also found that higher maternal warmth was a moderator, weakening the positive relation between power assertive discipline and children's emotional reactivity, which aligns with previous research on the role of warmth as a support or buffer in disciplinary interactions (Deater‐Deckard et al, 2006; McKee et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has documented that higher power assertive discipline is associated with children's noncompliance (Crockenberg & Litman, 1990; Xu et al, 2021), whereas less assertive strategies (e.g., verbal instructions and gentle guidance) predict more compliance (Feldman & Klein, 2003). Contrary to our hypothesis, we did not find a significant relation between power assertiveness and observed noncompliance in toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…The current study used a standardized and well-validated measure to code observed parent prosocial talk and negations (DPICS-IV; Bagner & Eyberg, 2007), but as we noted in the introduction, we did not look at commands and questions given the mixed nature of existing literature on these categories. Some research suggests that direct parent commands are associated with child noncompliance and defiance and are often seen as parent behaviors to avoid because the lead is taken away from the child (Bagner & Eyberg, 2007; Heflin et al, 2020; Kuczynski et al, 1987; Xu et al, 2021). Other research shows that providing commands through management language, such as using suggestions, is positively associated with children’s number talk (Clements et al, 2021).…”
Section: Discussionmentioning
confidence: 99%